2015
DOI: 10.5702/massspectrometry.a0042
|View full text |Cite
|
Sign up to set email alerts
|

Conifer-Derived Monoterpenes and Forest Walking

Abstract: Conifer and broadleaf trees emit volatile organic compounds in the summer. e major components of these emissions are volatile monoterpenes. Using solid phase microextraction ber as the adsorbant, monoterpenes were successfully detected and identi ed in forest air samples. Gas chromatography/mass chromatogram of monoterpenes in the atmosphere of a conifer forest and that of serum from subjects who were walking in a forest were found to be similar each other. e amounts of α-pinene in the subjects became several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…To our knowledge, only one study has analyzed the absorption of monoterpenes in blood after forest exposure, by identifying the monoterpene species present in a coniferous forest atmosphere in serum samples of individuals after walking in the forest [30]. The study demonstrated an increase in the amount of α-pinene in the serum after the individuals walked in the forest as well as differences in monoterpene composition and abundance between coniferous and broad-leaved forest air [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one study has analyzed the absorption of monoterpenes in blood after forest exposure, by identifying the monoterpene species present in a coniferous forest atmosphere in serum samples of individuals after walking in the forest [30]. The study demonstrated an increase in the amount of α-pinene in the serum after the individuals walked in the forest as well as differences in monoterpene composition and abundance between coniferous and broad-leaved forest air [30].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study has analyzed the absorption of monoterpenes in blood after forest exposure, by identifying the monoterpene species present in a coniferous forest atmosphere in serum samples of individuals after walking in the forest [30]. The study demonstrated an increase in the amount of α-pinene in the serum after the individuals walked in the forest as well as differences in monoterpene composition and abundance between coniferous and broad-leaved forest air [30]. In addition, Lee et al (2018) reported that the mean atmospheric concentration of monoterpenes at a 1.5-m height was higher in a natural than a tended forest [8], suggesting that vegetation characteristics derived from management may affect terpenes' concentrations under the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that inhaling oils containing terpenes significantly decreased SBP, DBP and cortisol levels [86]. Surprisingly, as far as we know, only one study has analyzed the absorption of terpenes in blood after forest exposure [87]. The authors of this study identified the monoterpenes species present in coniferous-forest atmosphere in serum samples of the subjects who were walking in the forest [87].…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, as far as we know, only one study has analyzed the absorption of terpenes in blood after forest exposure [87]. The authors of this study identified the monoterpenes species present in coniferous-forest atmosphere in serum samples of the subjects who were walking in the forest [87]. They also identified an increase in the amount of alpha-pinene in the serum after the subjects walked in the forest as well as differences in monoterpene composition and abundance between coniferous and broad-leaved forests air [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation